Bipedicular percutaneous kyphoplasty versus unipedicular percutaneous kyphoplasty in the treatment of asymmetric osteoporotic vertebral compression fractures: a case control study - Lei Liu; Feifei Song; Jie Shang; Jianwei Zhang; Chao Ma; Guangpu Liu; Meng Han (BMC Surgery, 2023)
Abstract Background Bipedicular/unipedicular percutaneous kyphoplasty are common treatments for OVCF, and there are no studies to show which is more beneficial for AVCF. The purpose of this study was to investigate the clinical efficacy of BPKP or UPKP in the treatment of AVCF. Methods The clinical data of AVCF patients treated by PKP were retrospectively analyzed. They were divided into two groups according to the surgical approach. General demographic data, perioperative complications, and general information related to surgery were recorded for both groups. The preoperative and postoperative vertebral height difference, vertebral local Cobb angle, lumbar pain VAS score and lumbar JOA score were counted for both groups. The above data were compared preoperatively, postoperatively and between the two groups. Results 25 patients with AVCF were successfully included and all were followed up for at least 12 months, with no complications during the follow-up period. 10 patients in the BPKP group and 15 patients in the UPKP group, with no statistically significant differences in general information between the two groups. The VAS scores of patients in the BPKP group were lower than those in the UPKP group at 12 months after surgery, and the differences were statistically significant, and there were no statistically significant differences between the two groups at other follow-up time points. In the BPKP group, 80% of patients had symmetrical and more homogeneous bone cement dispersion. 50% of patients in the UPKP group had a lateral distribution of bone cement and uneven bone cement distribution, and the difference in bone cement distribution between the two groups was statistically significant. Conclusion For the treatment of AVCF, the clinical efficacy of both surgical approaches is basically the same. The distribution of cement is more symmetrical and uniformly diffused in the BPKP group, and the clinical efficacy VAS score is lower in the long-term follow-up. Bipedicular percutaneous kyphoplasty is recommended for the treatment of AVCF. The ethical review batch number XZXY-LJ-20161208-047.